Don’t Ask, Don’t Tell: A Study on Whistleblowing Behavior in Indonesia State-owned Enterprises - Firmansah, Haikal; Rahajeng, Dian Kartika (The Indonesian Journal of Accounting Research, 2024)
Employees or subordinates can potentially engage in unethical behavior with their superiors both for themselves and their superiors, even though it can be detrimental to the organization as a whole. This study examines perceived supervisor support's effect on whistleblowing intentions through employee reciprocity. The method used was an online survey via Google Forms to employees of Indonesian state-owned enterprises. Of the 309 questionnaires obtained, only 279 questionnaires could be analyzed using a two-stage Partial Least Square Structural Equation Modeling (PLS-SEM) technique to test the hypotheses. The results show that perceived supervisor support does not directly affect whistleblowing intentions; it has an indirect and significant negative effect on whistleblowing intentions only through employee reciprocity. The findings of this study are expected to contribute theoretically and empirically to the fields of management accounting and business ethics.